Market Penetration Strategy in Direct Sales in Achieving Sales Targets for Candied Fruit Products (Case Study of Inavbaf Fruit's Business in Palu City) - Angelina; Thahir, Harifuddin (Journal of Humanities, Community Service, and Empowerment, 2024)
The research aims to determine the application of market penetration strategies in the sales of candied fruit products and to find out why Inavbaf Fruit uses market penetration strategies. Descriptive qualitative research method. This research uses primary data. Primary data was obtained from interviews, observation, and documentation. The data collection process has been carried out for 4 (four) months, starting from September 2023 to December 2023. The research location was conducted at the Inavbaf Fruit business in Jl. Mango No.02 RT/RW 001/001, Labuan Lelea Village. Regency. Donggala, Central Sulawesi. The market penetration strategy in Inavbaf Fruit's Business is included in marketing that uses the Rapid Penetration Strategy. This strategy is carried out by setting low product prices and high promotional activities. The research results show that Inafbav Fruit's market penetration strategy in terms of promotion has been promoting through social media, Facebook, WhatsApp, and advertising via Instagram by distributing real videos, distributing brochures to Tadulako University students, and advertising used by Inavbaf Fruit for direct sales of candied fruit products. It can help in achieving the sales target of 300 packs per month.